Pengenalan Huruf Hijaiyah Braille Pada Penyandang Tunanetra Lansia - Dzulfikar Akbar Romadlon; Tri Wahyu Rohmatdiyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the introduction of Braille hijaiyah letters for the visually impaired, as well as the challenges faced during this process. Despite various obstacles, visually impaired learners remain determined to study the words of Allah in their later years, so that the teachings of the Qur’an can serve as guidance in their daily lives. This research employs a qualitative method. The subjects of the study are teachers from the KBM Taman District participating in the PERTUNI program. The data collection techniques used include observation, interviews, and documentation. The findings reveal that learning is conducted through a combination of classical and individual approaches, utilizing both teaching aids and the read-listen technique. Although there are challenges, such as limited memory capacity among participants—most of whom are elderly—the program continues to run effectively and adaptively. Learning media such as the Braille Qur’an have proven to be effective in introducing hijaiyah letters to visually impaired learners. This program demonstrates that inclusive Qur’anic education can be accessed by all groups, including those with visual disabilities, through appropriate methods and a supportive learning environment.